Testing of the Prefabricated Reinforced Concrete Pillars - Šimek, Ondřej; Daněk, Petr; Zich, Miloš; Nečas, Radim; Janda, Miloslav (Solid state phenomena, 2020)
The subject of the article is the introduction of the results of the first series of tests of precast reinforced concrete pillars. These are the pillars simulating parts of walls that can, for example, form in the precast wall of residential buildings after an opening has been carved. The pillars are variously reinforced: from the simple reinforcement with wire mesh, to the reinforcement with standard reinforcement bars. Depending on the type of reinforcement and the type of loading, the deformation and tension of the individual pillars are studied. All of the pillars failed due to local compression of the concrete, a transversal tensile failure occurred in all cases.